Determining the potential barriers to ERP system adoption : a study on SMEs in Klang Valley / Emilia Md Noah - Md Noah, Emilia (2005)
The Enterprise Resource Planning (ERP) system is an integrated set of programs that provide support for core organizational activities such as manufacturing and logistics, finance and accounting, sales and marketing, and human resources (Aladwani, 2001). The Organizational Capacity to Change model, proposed by Gretzel and Fesenmaier (2000) was used in this paper. Particularly for this research, to identify the potential barriers to ERP system adoption, four variables were used, which are cultural factor, environmental factor, leadership and business complexity. Finding of survey found that cultural factor and leadership factors are the significant barriers to ERP system adoption.